Mammalian diversity in West Java, Indonesia - TEGUH HUSODO; SYA SYA SHANIDA; PUPUT FEBRIANTO; M PAHLA PUJIANTO; ERRI N MEGANTARA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Husodo T, Shanida SS, Febrianto P, Pujianto MP, Megantara EN. 2019. Mammalian diversity in West Java, Indonesia. Biodiversitas 20: 1846-1858. Protected forests in West Java are wider than conservation forests, whereas mammalian diversity in protected forests is as high as mammalian diversity in conservation forests. Mammals in protected forests are not protected by regional protection regulations, while anthropogenic factors in Java are quite high. This is possible that mammals who have high conservation status will experience local extinction. This study aims to determine (i) the composition of mammalian species and (ii) the species that are always found in studies of mammalian diversity in West Java. The study was conducted through a qualitative approach by combining several methods such as interview, camera trapping, sign survey, observation and transect, and collapsible traps. Mammalia in West Java found 54 species, 21 families, and nine orders with details of three species of Artiodactyla, 12 species of Carnivores, seven species of Chiroptera, one species of Dermoptera, one species of Euphotyphla, one species of Pholidota, five species of Primates, 21 species of Rodentia, and three species of Scandentia. The species that are always found in all study locations are nine species, including wild boar, Javan leopard, leopard cat, Javan mongoose, oriental small-clawed otter, Asian palm civet, grizzled leaf monkey, Javan langur, and Javan tree shrew. The results presented here may facilitate improvements in the mammalian diversity database, especially in the non-conservation area.